Anticancer Potential of Flavonoids: An Overview with an Emphasis on Tangeretin - Francisco Canindé Ferreira de Luna; Wallax Augusto Silva Ferreira; Samir Mansour Moraes Casseb; Edivaldo Herculano Correa de Oliveira (MDPI AG, 2023)
Natural compounds with pharmacological activity, flavonoids have been the subject of an exponential increase in studies in the field of scientific research focused on therapeutic purposes due to their bioactive properties, such as antioxidant, anti-inflammatory, anti-aging, antibacterial, antiviral, neuroprotective, radioprotective, and antitumor activities. The biological potential of flavonoids, added to their bioavailability, cost-effectiveness, and minimal side effects, direct them as promising cytotoxic anticancer compounds in the optimization of therapies and the search for new drugs in the treatment of cancer, since some extensively antineoplastic therapeutic approaches have become less effective due to tumor resistance to drugs commonly used in chemotherapy. In this review, we emphasize the antitumor properties of tangeretin, a flavonoid found in citrus fruits that has shown activity against some hallmarks of cancer in several types of cancerous cell lines, such as antiproliferative, apoptotic, anti-inflammatory, anti-metastatic, anti-angiogenic, antioxidant, regulatory expression of tumor-suppressor genes, and epigenetic modulation.